The Influence of Context and Emotional Intelligence Practice in Leading a Physical Fitness Testing Situation for Police Officers - McCallum, Kelly (Auckland University of Technology, 2020)
The concept of emotional intelligence (EI) has gained popularity in recent years due to its strong links to effective leadership. During the past few decades, various researchers have explored the importance of relationships and leadership achievement through the lens of EI (Pearman, 2011; Schneider, 2013). EI skills in sport leadership roles are crucial to maintaining strong relationships and positive outcomes. The purpose of this study is to explore the influence of context and EI practice in leading a physical fitness testing situation for police officers. In particular, the study examines the emotions present leading up to the police bi-annual Physical Competency Test (PCT) and the influences PEOs have on the psychological states of the police officers completing the test. A qualitative descriptive approach with semi-structured interviews was employed to gather data from five PEOs and five police officers. Data were analysed using thematic analysis and themes were drawn using the theoretical framework of Goleman’s (2004) five dimensions of EI and the Tripartite model of EI (Mikolajczak et al., 2009; Nelis et al., 2009). The findings of the study revealed that EI skills are essential within the PEO’s role due to the strong emotions present leading up to the PCT. Further, EI skills combined with effective communication can ultimately lead to trust within interpersonal relationships. The outcomes of this study clearly illustrate the need for the NZ Police to address the development of interpersonal skills within the PEO role specifically focusing on communication and building trust. Incorporating continuing education programmes aimed at developing EI and authentic collaboration skills should therefore develop strong interpersonal relationships within the role. This outcome is also relevant to the entire NZ Police force seeking to create effective leadership and strong relationships more broadly within the organisation.
Keywords: Emotional intelligence; Leadership; Police; Physical Competency Test; Communication; Trust; Physical Education Officer